Массовая культура - прогресс или регресс в жизни современного общества? - Гонцов, А.С. (Культура народов Причерноморья, 2014)
Целью статьи является определение роли массовой культуры в жизни современного
общества. Автором представлен краткий анализ теоретических моделей массовой культуры, созданных
в предшествующий период, предложена классификация современной массовой культуры, обосновано
значение массовой культуры в условиях глобализационных процессов современности. Целю статті є визначення ролі масової культури в житті сучасного суспільства. Автором
представлено короткий аналіз теоретичних моделей масової культури, створених у попередній період,
запропоновано класифікацію сучасної масової культури, обґрунтовано значення масової культури в
умовах глобалізаційних процесів сучасності. The purpose of is to define the role of popular culture in modern society. The author provides a brief
analysis of the theoretical models of mass culture created in the previous period, proposed a classification of
modern mass culture, justified the value of mass culture in a contemporary globalization processes.
The urgency of the problems caused by the mass culture of the role it plays in the modern world. The complexity
and contradictions of mass culture and its ability to transform under the influence of social, technical and
aesthetic factors, its mobility - all these circumstances necessitated the theoretical understanding of this
phenomenon to a new level, taking into account the previous experience of studying in the philosophical and
cultural literature.
In general, the study authors concluded that under current conditions, mass culture becomes the main sphere of
familiarizing society to cultural values, while becoming increasingly apparent transformation of popular culture
under the influence of cultural globalization.